Storytelling - Jane Beethoven; Rosanne Emery; Synía Carroll-McQuillan (Music magic video library, 1995)
Viewers learn how the voice and body can help tell stories expressively - - Hear storyteller, Synia, tell an African American story - - Enjoy a mime telling a story through dramatic movements - - Hear folksinger, Tom Chapin, sing a story song - - Discover how a ballet can tell a story through music and dance.